Dissolução de óxidos formados a altas temperaturas nos aços elétricos variando-se a temperatura e concentração da solução ácida na decapagem - Willian Francisco Leite (2008)
Evaluation of temperature and HCL concentration to optimise the pickling bath for 0,8% Si and 0,4% Al electrical steel. In laboratory, samples of this steel were immersed in recipient with HCL in different concentrations and temperature and generated pickling curves for eachsituation. The results showed that the best temperature for pickling was 75ºC and HCl free concentration was 10,30%.